Dinâmica em tempo real do efeito Kondo e resposta Raman eletrônica da fase com ordenamento de carga dos cupratos supercondutores - Moallison Ferreira Cavalcante (2023)
In this thesis we investigate the physics of two strongly correlated electron systems. The part I of this document is dedicated to the study of the real-time dynamics of the Kondo effect produced by a quench protocol. For it, we consider one or two metallic chains of interacting electrons (Hubbard chains) coupled to a magnetic impurity of spin 1/2. The quench protocol consists of assuming that, for times τ < 0, the chains are decoupled from the impurity, at τ = 0 the coupling is suddenly turned on and, for τ > 0 , the system evolves unitarily in time. We determine an analytical expression for the relaxation of the impurity magnetization in the time regime τ ≪ τK , where τK is the Kondo time. This result was confirmed by numerical calculations performed in our group. Based on these numerical results, we observe that the increase in the interaction U between the electrons in the chains leads to a faster decay of the impurity magnetization, showing that the electron-electron interaction favors the formation of the Kondo effect. Further we studied the time-dependent transport through the impurity, from which we determine, in the interacting case, an analytical expression for the time scale equivalent to the Kondo time. According to the expression we obtained, we conclude that the Kondo scale is reduced when U increases, in agreement with the numerical results mentioned above. In part II of this thesis we investigate the physics of superconducting cuprates, motivated by electronic Raman spectroscopy measurements of the charge density wave (CDW) phase observed in these materials. Through a phenomenological approach, we describe a charge order in the CuO2 plane. Analyzing the spectral properties of the system, we establish that the CDW phase should be more easily detectable in the ω > 0 (above the Fermi level) region of the local density of states. Our results for the B2g Raman response show a general dip-hump behavior, as actually seen in the experiments, which is independent of the system band structure. In contrast, the B1g Raman response is strongly band structure dependent. In the second part of the work, a more general model was proposed, based on the Yang-Rice-Zhang ansatz, which also takes into account the pseudogap (PG) phase. We conclude that the PG phase drives the doping dependence of the CDW energy scale, in agreement with the experiments. This result is suggestive of a PG phase governing the different energy scales of the exotic phases that appear in the underdoped region of the cuprate phase diagram.